2018
DOI: 10.1093/ibd/izy095
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Is a Pro-Inflammatory Damage-Associated Molecular Pattern Released During Active IBD

Abstract: We present the first evidence to show that mtDNA is released during active IBD. MtDNA is a potential mechanistic biomarker, and our data point to mtDNA-TLR9 as a therapeutic target in IBD. 10.1093/ibd/izy095_videoizy095.video5776747659001.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 41 publications
(43 reference statements)
5
78
0
1
Order By: Relevance
“…41 In a recent study, it was demonstrated that mtDNA released into the serum in IBD patients was recognized as a damage-associated molecular pattern (DAMP) potentially by toll-like receptor 9 (TRL9), and could provide a biomarker of inflammation. 56 Paneth cell defects in CD patients, a phenotype shown to associate with early disease recurrence after resection, 57 were shown to correlate with dysbiosis of the microbiome and reduced expression of a large cluster of oxidative phosphorylation genes, 58 suggesting patients with Paneth cell defects may have altered mucosal mitochondrial function but this was not further elucidated. Recent reports on the pediatric RISK stratification study using RNA sequencing analysis on CD inflamed biopsies demonstrated that patients who were at risk of structuring, but upon follow-up through 36 months remained complication free, exhibited an enriched mitochondrial function gene signature compared to those patients who developed complications.…”
Section: Mitochondrial Dysfunction and Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…41 In a recent study, it was demonstrated that mtDNA released into the serum in IBD patients was recognized as a damage-associated molecular pattern (DAMP) potentially by toll-like receptor 9 (TRL9), and could provide a biomarker of inflammation. 56 Paneth cell defects in CD patients, a phenotype shown to associate with early disease recurrence after resection, 57 were shown to correlate with dysbiosis of the microbiome and reduced expression of a large cluster of oxidative phosphorylation genes, 58 suggesting patients with Paneth cell defects may have altered mucosal mitochondrial function but this was not further elucidated. Recent reports on the pediatric RISK stratification study using RNA sequencing analysis on CD inflamed biopsies demonstrated that patients who were at risk of structuring, but upon follow-up through 36 months remained complication free, exhibited an enriched mitochondrial function gene signature compared to those patients who developed complications.…”
Section: Mitochondrial Dysfunction and Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…Such a milieu can also shape newly arriving inflammatory monocytes, monocyte-macrophage function, their survival, and their phenotype, and further factors that influence the host's highlighted the mitochondria as the major previously unknown "jigsaw piece" in inflammation 103 . Mitochondrial dysfunction has long been implicated in UC, as far back as 1980 104,105 (reviewed by Novak et al 106 ), but new data from the last 3 years have re-focused this concept 100,107,108 . Such dysregulation of genes that control mitochondrial function have been shown in earlier colonic microarray studies in UC 109 .…”
Section: Abnormal Immune Response: Innatementioning
confidence: 99%
“…Functional studies show that mitochondria are sited in a uniquely damaging environment (in the colon, more so than other tissue sites) 107,110 . Loss of mitochondrial homeostasis (including mitophagy and the autophagic removal of damaged mitochondria-IBD GWAS susceptibility genes PARK7 and LRRK2) can lead to defective energy production 111 , increased mitochondrial oxidative stress 107 , and even the release of mitochondrial products (mitochondrial DNA) as pro-inflammatory DAMPs 108,112 . These lines of evidence contribute to key UC themes such as epithelial dysfunction, the pro-inflammatory mucosal milieu, and direct triggers of the inflammatory response.…”
Section: Abnormal Immune Response: Innatementioning
confidence: 99%
“…Most of the studies demonstrated the interaction of mitochondrial DNA with TLR9 using class A ODNs. Following bacterial infection or leakage of mitochondrial DNA, TLR9 senses CpG DNA and drives immune responses [27,28] by activating downstream signaling cascades such as leucine-rich repeat pyrin domain containing 3 (NLRP3) inflammasomes, interferon regulatory factor (IRF)-dependent type 1 IFN, and pro-inflammatory nuclear factor kappa B (NFκB) [29].…”
Section: Mitochondrial Dna and Toll-like Receptormentioning
confidence: 99%